Equipping the Romanian army with French material. Financial aspects - Nicolescu, Andrei (Technium Social Sciences Journal, 2023)
Throughout the interwar period, France was Romania's largest supplier of arms and combat equipment. This was due to several factors that made the French defence industry the most attractive market for procurement in this field. The financial arrangements in which the French government showed flexibility, the fact that the French industry was one of the most advanced and complex in the world, being able to supply armaments for all the Romanian army's compartments and the readiness to provide its manufacturing plans to Romanian arms industry kept France in first place in the preferences of the Romanian government.